Food stories. Globalization and social integration as an aspect of eating. Customer cases from Alanya Import in Tromsoe - Lågeide, Eline A. (UiT Norges arktiske universitet, 2016)
Det finnes eksamensfilm Food stories, som etter kandidatens ønske ikke er tilgjengelig i Munin. Abstract thesis The purpose of this thesis is to discuss how the study of food relations can contribute to an insight in to the social dynamics of integration and globalisation processes. The empirical data is primarily based on a three-month fieldwork at Alanya Import, an international grocery shop at Storgata in Tromsø, Norway. I followed different customers and food commodities from Alanya Import to various kitchens in Tromsø. My research question as a starting point is how they relate to food from their homeland. The national, cosmopolitan and international are some of the belongings that are being expressed through grocery shopping, cooking and eating. My point of departure was to enlighten the anthropological insight that globalisation does not lead to cultural homogeneity, but new variation patterns. Further - how global processes are understood locally. My argument is that the senses are a highly important aspect of the understanding of complex identity processes in a complex urban space. It is a study of how particular food commodities are connected to memories and emotions, through senses and stories. I will argue how the camera is an excellent tool in doing research on the mentioned themes. Key words: Anthropology, visual anthropology, ethnographic film, food commodities, senses, taste, smell, memories, non-verbal knowledge, visual and invisible knowledge, integration, globalization, cosmopolitanism, multiculturalism, International shop, International city, Tromsø, north of Norway Synopsis FOOD STORIES Food Stories is a film that explores how particular food commodities are related to memories and emotions. The film is an outcome of a three-month fieldwork at Alanya Import, a greengrocery shop at Storgata in Tromsø, Norway. Different customers and goods are being followed through daily grocery shopping, cooking and sharing a meal. The film’s point of departure is how the customers relate to their food ...